Functional overlap between conserved and diverged KH domains in Saccharomyces cerevisiae SCP160 - Brykailo, Melissa A. (Oxford University Press, 2007)
The K homology (KH) domain is a remarkably versatile and highly conserved RNA-binding motif. Classical KH domains include a characteristic pattern of hydrophobic residues, a Gly-X-X-Gly (GXXG) segment, and a variable loop. KH domains typically occur in clusters, with some retaining their GXXG sequence (conserved), while others do not (diverged). As a first step towards addressing whether GXXG is essential for KH-domain function, we explored the roles of conserved and diverged KH domains in Scp160p, a multiple-KH-domain-containing protein in Saccharomyces cerevisiae. We specifically wanted to know (1) whether diverged KH domains were essential for Scp160p function, and (2) whether diverged KH domains could functionally replace conserved KH domains. To address these questions, we deleted and/or interchanged conserved and diverged KH domains of Scp160p and expressed the mutated alleles in yeast. Our results demonstrated that the answer to each question was yes. Both conserved and diverged KH domains are essential for Scp160p function, and diverged KH domains can function in place of conserved KH domains. These findings challenge the prevailing notions about the requisite features of a KH domain and raise the possibility that there may be more functional KH domains in the proteome than previously appreciated.